Triggering voltage for post-breakdown random telegraph noise in HfLaO dielectric metal gate metal-oxide-semiconductor field effect transistors and its reliability implications - Liu, W. H. (2013)
We report a triggering voltage Vtrig for observing gate leakage current (Ig) random telegraph noise (RTN) in the post-breakdown regime of HfLaO dielectric metal gate stacks. Vtrig, the onset voltage to observe RTN in degraded dielectrics, is highly dependent on breakdown hardness, which is controlled by the leakage current compliance (Igl). This dependence is qualitatively analyzed using a percolation dilation model, where generation of additional traps either at different energy levels or spatial locations gives lower Vtrig at higher Igl. The magnitude of Vtrig can be used as a direct indication of the impact of RTN on the performance of the transistor at device level, when Vtrig is evaluated by comparing with the device operating voltage.